Arctic Entrance: Opening the door to alternative trajectories for Indigenous housing through a decolonizing of planning practice - Stanford, Harriet (UiT Norges arktiske universitet, 2021)
Indigenous communities across Canada are facing a crisis in housing. In response, new and innovative designs, policies, and programs are being developed in attempt to shift away from harmful colonial-imposed models to ones that advance autonomy, healthy living, and cultural revitalization. This important shift has sparked debate and speculation about what a reclaiming or “decolonization” of planning looks like in practice. To explore what this emergent planning paradigm means in the context of rural, remote, and northern Indigenous communities, I interviewed experts working in or with Indigenous communities across Canada and Alaska, USA, in addition to undertaking case study and action research with the First Nation of Na-cho Nyäk Dun in Yukon, Canada. In contributing to established principles of good planning with Indigenous communities, my research suggests that a decolonized approach to housing planning is one that is inclusive off all community groups, integrates multiple objectives and needs, is sensitive to the surrounding landscape, builds on past work, sparks creativity and innovation, enables better understanding of both possibilities and trade-offs, and creates tangible and immediate change on the ground while acting with a long-term focus. My findings also suggests that there are particular planning considerations that should be taken into account when working in the north, and that planning as a practice should be reflexively critiqued, rethought, and transformed if it is to serve in support of communities in their self-determined transformation.